THE RETURN OF CHILDREN OF FOREIGN FIGHTERS - Rrotani, Antonella (Université d'Ottawa | University of Ottawa, 2021)
The international community faces several complex and difficult challenges related to the foreign fighters detained in northeast Syria, particularly the thousands of non-Syrian children. The long-term detention of these children in Syrian camps is deeply problematic for humanitarian and security reasons. The following paper will provide the government of Canada recommendations through research and analysis when developing policies concerning the repatriation of children of foreign fighters. The document will provide an analysis of the key issues about the possible return of children of foreign fighters in their home country through diverse literature. It examines the current de-radicalization and rehabilitation programs available in the UK, Australia and Canada and the need for more experimentation on the topic. The purpose of this paper is to create a holistic understanding of children of foreign fighters, to develop meaningful policy reforms, to ensure the well-being of these minors and the security of the rest of the population.